Américo Paredes : culture and critique - Limón, José Eduardo (Jack and Doris Smothers series in Texas history, life, and culture ;, 2012)
"A rich critical study of the literary legacies bestowed by the late Américo Paredes (1915-1999), and the intellectual paths he created as a distinguished folklore scholar and one of the forebears of Mexican American Studies."--Project Muse.